2021
DOI: 10.1016/j.ncrna.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia related long non-coding RNAs in ischemic stroke

Abstract: With high rates of mortality and disability, stroke has caused huge social burden, and 85% of which is ischemic stroke. In recent years, it is a progressive discovery of long non-coding RNA (lncRNA) playing an important regulatory role throughout ischemic stroke. Hypoxia, generated from reduction or interruption of cerebral blood flow, leads to changes in lncRNA expression, which then influence disease progression. Therefore, we reviewed studies on expression of hypoxia-related lncRNAs and relevant molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs), novel noncoding RNAs with a length of over 200 nucleotides, play an essential part in inflammatory responses and diseases [ 19 ]. Reportedly, hypoxia and ischemia in the aftermath of lessened or interrupted cerebral blood flow can bring about alterations in the profiles of many lncRNAs in brain tissues, hence influencing disease progression [ 20 23 ]. lncRNA MIR497HG (MIR497HG), a member of the lncRNA family, targets the miRNA-128-3p/SIRT1 axis to suppress proliferation and migration in human retinal endothelial cells elicited by high glucose [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs), novel noncoding RNAs with a length of over 200 nucleotides, play an essential part in inflammatory responses and diseases [ 19 ]. Reportedly, hypoxia and ischemia in the aftermath of lessened or interrupted cerebral blood flow can bring about alterations in the profiles of many lncRNAs in brain tissues, hence influencing disease progression [ 20 23 ]. lncRNA MIR497HG (MIR497HG), a member of the lncRNA family, targets the miRNA-128-3p/SIRT1 axis to suppress proliferation and migration in human retinal endothelial cells elicited by high glucose [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was previously found that the immune response of monocytes and the replication of the COVID-19 virus require the support of aerobic glycolysis [ 136 ]. The transcription factor hypoxia-inducible factor 1-alpha (HIF-1a) can induce glycolysis, leading to a pro-inflammatory state in monocytes infected with COVID-19 [ 137 ]. It has also been previously found that HIF1A stabilizing long non-coding RNA (HISLA) in macrophages provides stability to HIF-1a by inhibiting its binding to the prolyl hydroxylase domain-containing protein 2 (PHD2) protein, thereby preventing its degradation and thus maintaining continuous activation of the aerobic state in tumor cells through HIF-1a signaling [ 138 ].…”
Section: Non-coding Rnas In Covid-19mentioning
confidence: 99%
“…They also act as structural components in protein complex assembly and serve as competing endogenous RNAs (ceRNAs) to modulate miRNA functions [23,30]. In this regard, lncRNAs can inhibit or activate target genes, by directly binding to them or by recruiting transcription factors and thus modulating many cellular processes, including cell proliferation, differentiation, apoptosis, autophagy, angiogenesis, and immune response [31,32].…”
Section: Introductionmentioning
confidence: 99%